On estimates for the number of negative eigenvalues of two-dimensional Schrodinger operators with potentials supported by Lipschitz curves - Karuhanga, martin (My University, 2017)
In this paper we present quantitative upper estimates for the number of negative eigenvalues of a two-dimensional Schrodinger operator with potential supported by an unbounded Lipschitz curve. The estimates are given in terms of weighted L 1 and Llog L type Orlicz norms of the potential AA
Keywords: Negative eigenvalues; Schrodinger operators; Lipschitz curves